(3GdGSJZdGd GdLfSj aj GdGJLGQ HGdHTQ hJWHjbg Ydi GdbGUQGJ (B/ s - (3eMehO eMeO GdSYjO CMeOs; (3MSfjf EHQGgje UGdM YHjO (B: s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2022)
(3ai GdBhfI GdCNjQI(B: (3GfJTQJ XGgQI GdGJLGQ HGdHTQ(B: (3h HOCJ JfJTQ Ydi GdeSJhjjf GdYGdei h GdeMdi(B: (3dOQLI Cfg dG jecf JMOjO eOi GfJTGQ gPg GdXGgQI(B. (3JTed CTcGd GdGJLGQ HGdHTQ GdSNQI hGdYHhOjI h JLGQI GdCYVGA GdHTQjI h GSJZdGd GdCWaGd(B. (3GdLRA GdChd; LQGFe GdGSJZdGd GdLfSi ddbGUQGJ(B. (3CfgG JfWhi Ydi CQcGf LQjeI GdGJLGQ HGdHTQ HeG ai Pdc; ChdkG(B: (3GdYfUQ GdeaJQV(B: (3h gh TNUjI GdTNU cVMjI(B: (3h KGfkjG(B: (3GdYfUQ GdeGOi(B: (3h gh cd GdYfGUQ GdeGOjI GdJi jNdbgG GdLGfi ef NdGd Sdhcg(B. (3GdLRA (B2(3; GdMeGjI GdELQGFjI h GdOhdjI dLQGFe GdGSJZdGd GdLfSi(B. (3h HPdJ GdOhdI GdeUQjI GdYOjO ef GdLghO decGaMI GdGJLGQ HGdHTQ ef NdGd EfTGA GddLfI GdJfSjbjI GdhWfjI decGaMI GdGJLGQ HGdHTQ h YedJ Ydi EfTGA UfOhb GdVMGjG deSGYOI VMGjG LQGFe GdGJLGQ HGdHTQs
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI, (B2022.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI UaMGJ (B278 - 294.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdGJLGQ HGdHTQs; (3GdGSJZdGd GdLfSjs; (3GdbGUQGJs; (3GdSdhc GdELQGejs; (3GdGYJOGA GdLfSjs; (3GdGSJOQGLs; (3GdEZhGAs; (3GdHZGAs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs